Pengaruh geometri peledakan terhadap penggunaan bahan peledak di pit merandai PT. Cipta Kridatama jobsite PT. Bukit Baiduri Energi. Kabupaten kutai Kartanegara Provinsi Kalimantan Timur (Jurnal Geologi Pertambangan (JGP), 2021)
ABSTRACT The overburden and coal stripping activity is carried out by dredging and if the material is classified as hard, then the blasting method is used, because this system is considered more efficient and economical than using the ripping method. The rock conditions from one place to another will be different even though they may be of the same type. This is caused by the rock genesis process which will affect the rock mass characteristics physically (density, water content, porosity) and mechanically (compressive & tensile strength).It is also necessary to observe the appearance of geological structures, such as faults, joint discontinuities and so on in rocks. Such geological conditions will affect blastability. Of course, in rocks that are relatively compact and without any geological structure as above, where the amount of explosives needed will be more for a certain amount of production, compared to rocks that have fractures. The amount of explosives is called the specific charge or Powder Factor (PF) which is the amount of explosive used for each blasting product (kg/bcm). Prior to implementing a blasting work decision, it is necessary to first consider the selection of explosives and factors that affect the results of the explosion.To achieve success in dismantling the overburden using the drilling and blasting method is certainly not easy, but one must go through experiments by reviewing the blasting parameters and finally get satisfactory results. The blasting geometry consists of space, burden, level height, depth of blast hole column, stemming, length of column filled with explosives, and subdrilling. There are several empirical ways to calculate blast geometry that have been introduced by experts, such as R.L. Ash (1967), Langefors (1978), Konya (1972), Anderson (1952), Foldesi (1980), ICI-Explosive, and others.  Keywords: Geometry blasting, Explosives, blasting production target, Fragmentation.